2021
DOI: 10.5812/jjm.114473
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of Carbapenem-Resistant Klebsiella pneumoniae Isolates Producing blaVIM, blaNDM, and blaIMP in Clinical Centers in Isfahan, Iran

Abstract: Background: The emergence and spread of metallo-beta-lactamase (MBL)-producing Klebsiella pneumoniae are growing global public health concerns. One of the most common mechanisms of carbapenem resistance is the production of MBLs, including Verona Integron-encoded Metallo-beta-lactamase (VIM), imipenemase (IMP), and New Delhi metallo-beta-lactamase (NDM). Objectives: This study aimed to investigate MBLs production among K. pneumoniae isolates. Methods: In this study, 240 K. pneumoniae isolates were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
0
1
Order By: Relevance
“…Concurring with our finding, a study in India found bla NDM in 28.8% and bla VIM in 17.7% of K. pneumoniae isolates among VAP patients [ 32 ]. However, a study from Iran revealed that bla VIM was the most prevalent gene (13.6%), while both bla IMP and bla NDM were only detected in two K. pneumoniae isolates [ 33 ], which is not in concordance with our findings.…”
Section: Discussioncontrasting
confidence: 79%
“…Concurring with our finding, a study in India found bla NDM in 28.8% and bla VIM in 17.7% of K. pneumoniae isolates among VAP patients [ 32 ]. However, a study from Iran revealed that bla VIM was the most prevalent gene (13.6%), while both bla IMP and bla NDM were only detected in two K. pneumoniae isolates [ 33 ], which is not in concordance with our findings.…”
Section: Discussioncontrasting
confidence: 79%
“…Carbapenemase genes were detected in 55 isolates, with bla OXA-48 (63.5%) as the predominant carbapenemase gene, followed by bla NDM (36.5%). Alizadeh et al 40 reported that bla VIM-1 as the most prevalent gene followed by bla IMP-1 and bla NDM-1 . This study suggested that PCR could be considered a suitable tool for the rapid identification of strains with high epidemic potential that may be required for local outbreak studies.…”
Section: Discussionmentioning
confidence: 99%